KRAS and TP53 mutations in bronchoscopy samples from former lung cancer patients. Issue 2 (6th June 2016) - Gao, Weimin; Jin, Jide; Yin, Jinling; Land, Stephanie; Gaither‐Davis, Autumn; Christie, Neil; Luketich, James D.; Siegfried, Jill M.; Keohavong, Phouthone
Abstract : Mutations in the KRAS and TP53 genes have been found frequently in lung tumors and specimens from individuals at high risk for lung cancer and have been suggested as predictive markers for lung cancer. In order to assess the prognostic value of these two genes' mutations in lung cancer recurrence, we analyzed mutations in codon 12 of the KRAS gene and in hotspot codons of the TP53 gene in 176 bronchial biopsies obtained from 77 former lung cancer patients. Forty‐seven patients (61.0%) showed mutations, including 35/77 (45.5%) in the KRAS gene and 25/77 (32.5%) in the TP53 gene, among them 13/77 (16.9%) had mutations in both genes. When grouped according to past or current smoking status, a higher proportion of current smokers showed mutations, in particular those in the TP53 gene ( P  = 0.07), compared with ex‐smokers. These mutations were found in both abnormal lesions (8/20 or 40%) and histologically normal tissues (70/156 or 44.9%) ( P  = 0.812). They consisted primarily of G to A transition and G to T transversion in both the KRAS (41/56 or 73.2%) and TP53 (24/34 or 70.6%) genes, consistent with mutations found in lung tumors of smoking lung cancer patients. Overall, recurrence‐free survival (RFS) among all subjects could be explained by age at diagnosis, tumor stage, tumor subtype, and smoking ( P  < 0.05, Cox proportional hazard). Therefore, KRAS and TP53 mutations were frequently detected in bronchial tissues of former lung cancer patients. However, the presence of mutation of bronchial biopsies was not significantly associated with a shorter RFS time. © 2016 Wiley Periodicals, Inc.